SOCIO-ECONOMIC FACTORS AND HEALTH FACILITY-RELATED FACTORS AFFECTING THE UTILIZATION OF ANC SERVICES AMONG WOMEN AGED 18-40 ATTENDING ANC AT KYANKWANZI HEALTH CENTER III. A CROSS-SECTIONAL STUDY. - Owembabazi, Moreen; Mpamize , Habert; Naggulu, Immaculate Prosperia; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2025)
Background The study aims to identify the Socioeconomic factors and health facility-related factors affecting the utilization of ANC services among women aged 18-40 attending ANC at Kyankwanzi Health Center III. Methodology A descriptive quantitative cross-sectional study design was used. The study targeted all pregnant mothers who attend ANC at Kyankwanzi Health Centre III aged between 18-40 years of age, with a sample size of 32 participants. Results The majority 14(43.7%) of the respondents were aged 18-24 years, while the least 2(6.3%) were 35-40 years. 14(43.7%) were self-employed and 6(18.8%) were formally employed. The majority 21(65.6%) mentioned receiving advice on pregnancy management as the most important reason for attending ANC. 28(87.5%) reported that financial constraints prevent them from attending ANC visits. 21(65.6%) reported that their cultural norms or traditions in the community do not affect their decision to seek ANC services. 18(56%) said their spouse or other family members play a role in deciding whether or not to attend ANC. 17(53.1%) said the distance to the health facility greatly affects the respondents’ ability to attend ANC visits regularly. 20(62.5%) have experienced mistreatment or disrespect from healthcare staff during an ANC visit. 22(68.7%) said that the availability of skilled healthcare providers at the facility impacted the decision to seek ANC. Conclusion Financial barriers, medical supply costs, inadequate support from partners and families, mistreatment, or perceived lack of respect from healthcare staff contribute to delays and missed ANC visits. Factors like perceived quality of care and interactions with healthcare providers also influenced ANC attendance. Recommendation Enhancing healthcare staff training to promote respectful, culturally sensitive care, focusing on improving patient-provider interactions and reducing instances of mistreatment.